About Outing: Public Discourse, Private Lives - Katheleen Guzman (Washington University Law Quarterly, 1995)
As Part II discusses, societal, personal, political, and legal double-binds plague homosexuality: Lesbians and gay men might be persecuted, but they do not deserve legal protection; they may be criminals, but their crimes often go unpunished; they merit no "special benefits," for they are just like everyone else; they suffer extra burdens, because "they are not like everyone else." Outing reveals these tensions created by life and law. Part III reveals that traditional tort doctrine and analysis lack any framework within which to remedy the harm. Part IV proposes internal legal reform to better accommodate the competing interests of freedom of speech and privacy, and suggests that the most potent and appropriate response to outing lies less in superficial reconstruction of tort doctrines than in drastic societal and legal reconceptualization of sexual orientation and its dynamics.
Keywords: Right of privacy; Freedom of speech; Homosexuality